:: Lucas Numbers and Generalized {F}ibonacci Numbers
:: by Piotr Wojtecki and Adam Grabowski
::
:: Copyright (c) 2004-2019 Association of Mizar Users

theorem :: FIB_NUM3:1
for a being Real
for n being Element of NAT st a to_power n = 0 holds
a = 0
proof end;

theorem Th2: :: FIB_NUM3:2
for a being non negative Real holds (sqrt a) * (sqrt a) = a
proof end;

theorem Th3: :: FIB_NUM3:3
for a being Real holds a to_power 2 = (- a) to_power 2
proof end;

theorem Th4: :: FIB_NUM3:4
for k being non zero Nat holds (k -' 1) + 2 = (k + 2) -' 1
proof end;

theorem Th5: :: FIB_NUM3:5
for a, b being Element of NAT holds (a + b) |^ 2 = (((a * a) + (a * b)) + (a * b)) + (b * b)
proof end;

theorem Th6: :: FIB_NUM3:6
for n being Element of NAT
for a being non zero Real holds (a to_power n) to_power 2 = a to_power (2 * n)
proof end;

theorem Th7: :: FIB_NUM3:7
for a, b being Real holds (a + b) * (a - b) = (a to_power 2) - (b to_power 2)
proof end;

theorem Th8: :: FIB_NUM3:8
for n being Element of NAT
for a, b being non zero Real holds (a * b) to_power n = (a to_power n) * (b to_power n)
proof end;

registration
coherence by FIB_NUM2:33;
coherence by FIB_NUM2:36;
end;

theorem Th9: :: FIB_NUM3:9
for n being Nat holds () + (tau to_power (n + 1)) = tau to_power (n + 2)
proof end;

theorem Th10: :: FIB_NUM3:10
for n being Nat holds () + (tau_bar to_power (n + 1)) = tau_bar to_power (n + 2)
proof end;

definition
let n be Nat;
:: Lucas numbers
func Lucas n -> Element of NAT means :Def1: :: FIB_NUM3:def 1
ex L being sequence of st
( it = (L . n) 1 & L . 0 = [2,1] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) );
existence
ex b1 being Element of NAT ex L being sequence of st
( b1 = (L . n) 1 & L . 0 = [2,1] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) )
proof end;
uniqueness
for b1, b2 being Element of NAT st ex L being sequence of st
( b1 = (L . n) 1 & L . 0 = [2,1] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) & ex L being sequence of st
( b2 = (L . n) 1 & L . 0 = [2,1] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) holds
b1 = b2
proof end;
end;

:: deftheorem Def1 defines Lucas FIB_NUM3:def 1 :
for n being Nat
for b2 being Element of NAT holds
( b2 = Lucas n iff ex L being sequence of st
( b2 = (L . n) 1 & L . 0 = [2,1] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) );

theorem Th11: :: FIB_NUM3:11
( Lucas 0 = 2 & Lucas 1 = 1 & ( for n being Nat holds Lucas ((n + 1) + 1) = () + (Lucas (n + 1)) ) )
proof end;

theorem Th12: :: FIB_NUM3:12
for n being Nat holds Lucas (n + 2) = () + (Lucas (n + 1))
proof end;

theorem Th13: :: FIB_NUM3:13
for n being Nat holds (Lucas (n + 1)) + (Lucas (n + 2)) = Lucas (n + 3)
proof end;

theorem Th14: :: FIB_NUM3:14
Lucas 2 = 3
proof end;

theorem Th15: :: FIB_NUM3:15
Lucas 3 = 4
proof end;

theorem Th16: :: FIB_NUM3:16
Lucas 4 = 7
proof end;

theorem Th17: :: FIB_NUM3:17
for k being Nat holds Lucas k >= k
proof end;

theorem :: FIB_NUM3:18
for m being non zero Element of NAT holds Lucas (m + 1) >= Lucas m
proof end;

registration
let n be Element of NAT ;
coherence
proof end;
end;

theorem :: FIB_NUM3:19
for n being Element of NAT holds 2 * (Lucas (n + 2)) = () + (Lucas (n + 3))
proof end;

theorem :: FIB_NUM3:20
for n being Nat holds Lucas (n + 1) = (Fib n) + (Fib (n + 2))
proof end;

theorem Th21: :: FIB_NUM3:21
for n being Nat holds Lucas n = () + ()
proof end;

theorem :: FIB_NUM3:22
for n being Nat holds (2 * ()) + (Lucas (n + 1)) = 5 * (Fib (n + 1))
proof end;

theorem Th23: :: FIB_NUM3:23
for n being Nat holds (Lucas (n + 3)) - (2 * ()) = 5 * (Fib n)
proof end;

theorem :: FIB_NUM3:24
for n being Nat holds () + (Fib n) = 2 * (Fib (n + 1))
proof end;

theorem :: FIB_NUM3:25
for n being Nat holds (3 * (Fib n)) + () = 2 * (Fib (n + 2))
proof end;

theorem :: FIB_NUM3:26
for n, m being Element of NAT holds 2 * (Lucas (n + m)) = (() * ()) + ((5 * (Fib n)) * (Fib m))
proof end;

theorem :: FIB_NUM3:27
for n being Element of NAT holds (Lucas (n + 3)) * () = ((Lucas (n + 2)) |^ 2) - ((Lucas (n + 1)) |^ 2)
proof end;

theorem Th28: :: FIB_NUM3:28
for n being Nat holds Fib (2 * n) = (Fib n) * ()
proof end;

theorem :: FIB_NUM3:29
for n being Element of NAT holds 2 * (Fib ((2 * n) + 1)) = ((Lucas (n + 1)) * (Fib n)) + (() * (Fib (n + 1)))
proof end;

theorem :: FIB_NUM3:30
for n being Element of NAT holds (5 * ((Fib n) |^ 2)) - (() |^ 2) = 4 * ((- 1) to_power (n + 1))
proof end;

theorem :: FIB_NUM3:31
for n being Element of NAT holds Fib ((2 * n) + 1) = ((Fib (n + 1)) * (Lucas (n + 1))) - ((Fib n) * ())
proof end;

definition
let a, b be Nat;
:: original: [
redefine func [a,b] -> Element of ;
coherence
[a,b] is Element of
proof end;
end;

definition
let a, b, n be Nat;
func GenFib (a,b,n) -> Element of NAT means :Def2: :: FIB_NUM3:def 2
ex L being sequence of st
( it = (L . n) 1 & L . 0 = [a,b] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) );
existence
ex b1 being Element of NAT ex L being sequence of st
( b1 = (L . n) 1 & L . 0 = [a,b] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) )
proof end;
uniqueness
for b1, b2 being Element of NAT st ex L being sequence of st
( b1 = (L . n) 1 & L . 0 = [a,b] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) & ex L being sequence of st
( b2 = (L . n) 1 & L . 0 = [a,b] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) holds
b1 = b2
proof end;
end;

:: deftheorem Def2 defines GenFib FIB_NUM3:def 2 :
for a, b, n being Nat
for b4 being Element of NAT holds
( b4 = GenFib (a,b,n) iff ex L being sequence of st
( b4 = (L . n) 1 & L . 0 = [a,b] & ( for n being Nat holds L . (n + 1) = [((L . n) 2),(((L . n) 1) + ((L . n) 2))] ) ) );

theorem Th32: :: FIB_NUM3:32
for a, b being Nat holds
( GenFib (a,b,0) = a & GenFib (a,b,1) = b & ( for n being Nat holds GenFib (a,b,((n + 1) + 1)) = (GenFib (a,b,n)) + (GenFib (a,b,(n + 1))) ) )
proof end;

theorem Th33: :: FIB_NUM3:33
for a, b being Element of NAT
for k being Nat holds ((GenFib (a,b,(k + 1))) + (GenFib (a,b,((k + 1) + 1)))) |^ 2 = (((GenFib (a,b,(k + 1))) |^ 2) + ((2 * (GenFib (a,b,(k + 1)))) * (GenFib (a,b,((k + 1) + 1))))) + ((GenFib (a,b,((k + 1) + 1))) |^ 2)
proof end;

theorem Th34: :: FIB_NUM3:34
for a, b, n being Nat holds (GenFib (a,b,n)) + (GenFib (a,b,(n + 1))) = GenFib (a,b,(n + 2))
proof end;

theorem Th35: :: FIB_NUM3:35
for a, b, n being Nat holds (GenFib (a,b,(n + 1))) + (GenFib (a,b,(n + 2))) = GenFib (a,b,(n + 3))
proof end;

theorem Th36: :: FIB_NUM3:36
for a, b, n being Element of NAT holds (GenFib (a,b,(n + 2))) + (GenFib (a,b,(n + 3))) = GenFib (a,b,(n + 4))
proof end;

theorem :: FIB_NUM3:37
for n being Element of NAT holds GenFib (0,1,n) = Fib n
proof end;

theorem Th38: :: FIB_NUM3:38
for n being Element of NAT holds GenFib (2,1,n) = Lucas n
proof end;

theorem Th39: :: FIB_NUM3:39
for a, b, n being Element of NAT holds (GenFib (a,b,n)) + (GenFib (a,b,(n + 3))) = 2 * (GenFib (a,b,(n + 2)))
proof end;

theorem :: FIB_NUM3:40
for a, b, n being Element of NAT holds (GenFib (a,b,n)) + (GenFib (a,b,(n + 4))) = 3 * (GenFib (a,b,(n + 2)))
proof end;

theorem :: FIB_NUM3:41
for a, b, n being Element of NAT holds (GenFib (a,b,(n + 3))) - (GenFib (a,b,n)) = 2 * (GenFib (a,b,(n + 1)))
proof end;

theorem :: FIB_NUM3:42
for a, b, n being non zero Element of NAT holds GenFib (a,b,n) = ((GenFib (a,b,0)) * (Fib (n -' 1))) + ((GenFib (a,b,1)) * (Fib n))
proof end;

theorem :: FIB_NUM3:43
for n, m being Nat holds ((Fib m) * ()) + (() * (Fib n)) = GenFib ((),(),(n + m))
proof end;

theorem :: FIB_NUM3:44
for n being Element of NAT holds () + (Lucas (n + 3)) = 2 * (Lucas (n + 2))
proof end;

theorem :: FIB_NUM3:45
for a, n being Element of NAT holds GenFib (a,a,n) = ((GenFib (a,a,0)) / 2) * ((Fib n) + ())
proof end;

theorem :: FIB_NUM3:46
for a, b, n being Element of NAT holds GenFib (b,(a + b),n) = GenFib (a,b,(n + 1))
proof end;

theorem :: FIB_NUM3:47
for a, b, n being Element of NAT holds ((GenFib (a,b,(n + 2))) * (GenFib (a,b,n))) - ((GenFib (a,b,(n + 1))) |^ 2) = ((- 1) to_power n) * (((GenFib (a,b,2)) |^ 2) - ((GenFib (a,b,1)) * (GenFib (a,b,3))))
proof end;

theorem :: FIB_NUM3:48
for a, b, k, n being Element of NAT holds GenFib ((GenFib (a,b,k)),(GenFib (a,b,(k + 1))),n) = GenFib (a,b,(n + k))
proof end;

theorem Th49: :: FIB_NUM3:49
for a, b, n being Element of NAT holds GenFib (a,b,(n + 1)) = (a * (Fib n)) + (b * (Fib (n + 1)))
proof end;

theorem :: FIB_NUM3:50
for b, n being Element of NAT holds GenFib (0,b,n) = b * (Fib n)
proof end;

theorem :: FIB_NUM3:51
for a, n being Element of NAT holds GenFib (a,0,(n + 1)) = a * (Fib n)
proof end;

theorem :: FIB_NUM3:52
for a, b, c, d, n being Element of NAT holds (GenFib (a,b,n)) + (GenFib (c,d,n)) = GenFib ((a + c),(b + d),n)
proof end;

theorem :: FIB_NUM3:53
for a, b, k, n being Element of NAT holds GenFib ((k * a),(k * b),n) = k * (GenFib (a,b,n))
proof end;

theorem :: FIB_NUM3:54
for a, b, n being Element of NAT holds GenFib (a,b,n) = ((((a * ()) + b) * ()) + (((a * tau) - b) * ())) / (sqrt 5)
proof end;

theorem :: FIB_NUM3:55
for a, n being Element of NAT holds GenFib (((2 * a) + 1),((2 * a) + 1),(n + 1)) = ((2 * a) + 1) * (Fib (n + 2))
proof end;